Quality of chronic kidney disease management in primary care: a retrospective study - Van Gelder, Vincent A. (Scand J Prim Health Care, 2016)
BACKGROUND: Early detection and appropriate management of chronic kidney disease (CKD) in primary care are essential to reduce morbidity and mortality. AIM: To assess the quality of care (QoC) of CKD in primary healthcare in relation to patient and practice characteristics in order to tailor improvement strategies. DESIGN AND SETTING: Retrospective study using data between 2008 and 2011 from 47 general practices (207 469 patients of whom 162 562 were adults). METHOD: CKD management of patients under the care of their general practitioner (GP) was qualified using indicators derived from the Dutch interdisciplinary CKD guideline for primary care and nephrology and included (1) monitoring of renal function, albuminuria, blood pressure, and glucose, (2) monitoring of metabolic parameters, and alongside the guideline: (3) recognition of CKD. The outcome indicator was (4) achieving blood pressure targets. Multilevel logistic regression analysis was applied to identify associated patient and practice characteristics. RESULTS: Kidney function or albuminuria data were available for 59 728 adult patients; 9288 patients had CKD, of whom 8794 were under GP care. Monitoring of disease progression was complete in 42% of CKD patients, monitoring of metabolic parameters in 2%, and blood pressure target was reached in 43.1%. GPs documented CKD in 31.4% of CKD patients. High QoC was strongly associated with diabetes, and to a lesser extent with hypertension and male sex. CONCLUSION: KEY POINTS: Quality of care for chronic kidney disease patients in primary care can be improved. In comparison with guideline advice, adequate monitoring of disease progression was observed in 42%, of metabolic parameters in 2%, correct recognition of impaired renal function in 31%, and reaching blood pressure targets in 43% of chronic kidney disease patients. Quality of care was higher in patients with diabetes. Chronic kidney disease management may be improved by developing strategies similar to diabetes care.